(untitled) (Plant Tissue Culture and Biotechnology, 2018)
Cymbopogon schoenanthus subsp. proximus is a medicinal grass, the source of sesquiterpene proximadiol and is well known in folk medicine as renal antispasmodic. The effect of growth regulators, different sugar types, methyl jasmonate and vitamins on de novo organogenesis from seed cultures was studied. Among different concentrations of NAA and BA, 4 mg/l NAA in combination with 0.5 mg/l BA produced 100% callus induction. Both 1.0 and 4.0 mg/l NAA in combination with 0.5 mg/l BA yielded the highest number of shoots. High concentration of sucrose 6% was efficient in root induction from organogenic shoots. Sugar types at a constant concentration of 3% had a significant effect on raising shoot numbers. Different concentrations of methyl jasmonate, biotin and Ca-pantothenate showed a decline in de novo shoot induction, but root formation frequency and numbers were significantly improved with all concentrations used. Plant Tissue Cult. & Biotech. 28(2): 147-160, 2018 (December)